Philology in the Making - Kelemen, Pál,Pethes, Nicolas (Transcipt Verlag, 2019)
Cover; Table of contents; Introduction; 1. Theories; How We Read;
Keywords: Digital humanities; Humanities; Humanism; Philology; Humanities; Philosophy; Humanities; Social aspects; Philology; Study and teaching; SOCIAL SCIENCE; Popular Culture